Development of an On-Grid Low-Voltage Battery Energy Storage System with Balancing Dual-DC-Voltage Quasi Single-Stage Converter - Kumsuwan, Yuttana; Jarutus, Neerakorn (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2024)
With low-voltage (LV) battery energy storage systems (BESSs), the quasi single-stage converters (QSSCs) are utilized to reduce power consumption in two-stage conversion systems. Despite a good waveform quality of applying multilevel converters, the unbalancing voltage problems is possible to be contributed, such as decrease in grid quality and complexity in pulse-width-modulation (PWM). In this paper, it is the main challenge to solve these problems for developing the on-grid LV BESS with the QSSC. Balancing voltage control is proposed to control the dc-dc converter. As a result, the dual dc voltages are equalized. The system waveform quality and power quality can be improved. The PWM stage is then symmetrical and simplified. For more simplicity, the two-inphase carrier-based PWM is applied. The continuous non-sinusoidal scheme is preferred to not only provide the full dc utilization, but also improve the grid waveform quality in addition to the improvement from the proposed control method. Besides, the powers are simply controlled using the basic of the current vector control and decoupling from the balancing voltage control, resulting in the grid-connected enhancement without affecting the waveform quality. A 10-kW-microgrid-scale BESS is employed to validate the feasibility of the proposed system and its superiority over conventional systems.